1998
DOI: 10.1089/jwh.1998.7.849
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the Mature Woman

Abstract: Menopause is associated with myths about the death of sexual vitality. While menopause causes many women to experience vasomotor instability, problems with osteoporosis, urogenital aging, and increased risk of heart disease, these issues can now be addressed with hormonal replacement strategies or alternative therapies. The menopausal woman today can be relatively comfortable with regard to direct menopausal symptoms of estrogen deficiency as a result of medical therapies. Sexual health and intimacy should als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Psychiatric co-morbidity impacts sexual function to different degrees in each individual, with past sexual trauma, eating disorders, or histrionic personality disorder [54][55][56][57][58] having some impact on sexual function. As many as 70% of patients with depression report a decline in libido [59].…”
Section: Chapter 20mentioning
confidence: 99%
“…Psychiatric co-morbidity impacts sexual function to different degrees in each individual, with past sexual trauma, eating disorders, or histrionic personality disorder [54][55][56][57][58] having some impact on sexual function. As many as 70% of patients with depression report a decline in libido [59].…”
Section: Chapter 20mentioning
confidence: 99%
“…This decreased desire has been attributed to hormonal changes such as androgen deficiency (Guay, 2001;Levin, 2002) and poor physical fitness, along with psychosocial factors such as decreased self-image or feeling sexually unattractive (Morokoff, 1988;Myskow, 2002) and depression (Maartens, Knottnerus, & Pop, 2002;Myskow, 2002). Although there is general agreement in the literature regarding decreased desire being a salient perimenopausal symptom (Berentsen et al, 2001;Li et al, 2000;Myskow, 2002), Pariser and Niedermier (1998) reported that "studies of sexual function among perimenopausal and menopausal women do not demonstrate evidence of specific sexual dysfunction, such as delayed orgasm or loss of sexual desire" (p. 850). A full exploration of any changes in sexual desire is still warranted by therapists working with these individuals.…”
Section: )mentioning
confidence: 99%
“…Discomfort from insertional dyspareunia (i.e., pain during vaginal penetration) and occasional painful uterine contractions with orgasm, which occurs in some perimenopausal women, also affect the excitement and orgasm phases (Gelfand, 2000;Li et al, 2000;Sarrel, 2000). These changes not only adversely affect sexual desire but can also lead to a decrease in sexual activity (Capuzzi, 1982;Myskow, 2002;Pariser & Niedermier, 1998).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It is an amalgam of biomedical and psychosocial models, yet has added focus on culture. This model takes a holistic approach to sexual health, which is recommended by researchers and clinicians engaged in the study of midlife women (Pariser & Niedermier, 1998). It was originally outlined by Lee and colleagues (1994) as a way to examine the perimenopausal experience.…”
Section: Cultural View Of Perimenopausementioning
confidence: 99%